Housing Choices of Muslim Immigrants in Italy - Sungur, Ozden (European Scientific Journal, ESJ, 2016)
This paper aims to study housing choices of Muslim immigrants in Italy using micro level data collected by the ISMU Foundation. For this purpose, a probit model of home ownership is estimated using demographic variables such age, education, marital status, family characteristics, religion as well as financial variables measuring household expenses and financial difficulty. This is intended as a first step in uncovering household preferences for various investment alternatives among Muslim population in Western societies.